Analysis of Husband Support, Family, Friends dan Health Workers to The Use of MKJP in Women of Reproductive Age - Istifadatul Ilmiya; Ika Sulistiyawati (JURNAL KEBIDANAN KESTRA (JKK), 2022)
There are still fewer woman of reproductive age who use long term contraceptive methods compared to those who do not use MKJP. The choice of using MKJP can be influenced by social support, which can provide motivation, change the willingness and ability to solve challenges and provide security for contraceptive acceptors. The purpose of this study was to analyze the support of husbands, family, friends and health workers on the use of MKJP in women of reproductive age. This type of research is an observational analytic study using a cross sectional design. The samples in the study was 225 respondents. The data analysis used logistic regression test. The results showed that there was an effect of support from husbands, friends and health workers on the use of MKJP with p value <0.05 (p value =0.04, p value =0.04, p value =0.03). The conclusion in this study is that social support that can affect the use of MKJP in women of childbearing age is husband support, friend support and health worker support. Suggestions to further researchers are to add various other factors that can influence the selection and determination of the use of MKJP.